Prototipe Manajemen Bandwidth pada Jaringan Internet Hotel Harvani dengan Mikrotik RB 750r2 - Aan Restu Mukti; Rahmat Novrianda Dasmen (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
Harvani Hotel has 5 (five) floors, where each floor has 1 (one) Access Point (AP). All Access Points, servers and several Personal Computers (PCs) are connected to the RB 750r2 microtic router which is connected directly to the Internet Service Provider (ISP) so that all users are connected to the internet network. The problem that occurs is the uneven distribution of bandwidth so that the first user connected to the internet will get more bandwidth with the highest internet access speed. This causes interference to other users who feel the speed of internet access is very slow, which results in user inconvenience in using internet access. Therefore, bandwidth management is done in this research uses the action research method, where the prototype is focused on 5 Access Points by using ISP that provide bandwidth services of 2.5 Mbps and shared equally among 5 Access Points. From the testing results using the speedtest known that every AP only get the throughput between 100 - 400 kbps. This is providing that the bandwidth used of every AP does not expand 512 kbps and the bandwidth distribution of every AP has been ordered to remove the existence of user interest.